Characteristics of TSP and PM2.5 measured at Tokchok Island in the Yellow Sea - Lee, SB; Bae, GN; Moon, KC; Kim, YP (PERGAMON-ELSEVIER SCIENCE LTD, 2002)
Various air pollutants have been measured at Tokchok Island since April 1999. The Island is situated in the Yellow Sea, about 50 km from Incheon. This study was undertaken to help understand the levels of air pollution and their distribution characteristics over the Yellow Sea. The mass concentrations and chemical compositions, of total suspended particulates (TSP) and fine particles (PM2.5), measured up until March 2000 are discussed in this paper. The overall average mass concentrations for TSP and PM2.5 were about 37.2 and 18.7 mug m(-3), respectively, which were similar to, or lower than, those observed at other background sites in Kangwha and Taean, Korea. However, they are much lower than those observed at Qingdao in China. The low mass concentrations and major anthropogenic ion concentrations in aerosols collected at Tokchok Island show that local sources are not dominant. The estimated average fractions of non-sea-salt (nss) sulfate to total sulfate concentrations of TSP and PM2.5 are > 98% for each. This would suggest that sulfate is mainly affected by anthropogenic sources. If we consider the average mass ratio of PM2.5 to TSP, the mass fractions of anthropogenic species to PM2.5, and the molar ratio of nss sulfate to total nitrate, it may be possible to infer that a part of the anthropogenic species measured at Tokchok Island is transported from China. The characteristics of neutralization of nss sulfate, and the particle sizes of major ions, are also discussed. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: SALT SULFATE; AEROSOL; PARTICLE; NITRATE; CHINA; KOREA; NOX